PRESISI DAN AKURASI KROMATOGRAFI GAS DALAM PENETAPAN KADAR ASAM PROPIONAT DALAM PRODUKSI BAKERI (PRECISION AND ACCURACY OF GAS CHROMATOGRAPHY FOR DETERMINATION OF PROPIONIC ACID LEVELS IN BAKERY PRODUCT) - Nasril Fuad Hasan; Warsidah Warsidah; Gusrizal Gusrizal (Tanjungpura University, 2021)
Percission and accurate gas chromatographic method for determination of propionic acid in bakery products was developed. Bakery productswere directly extraction with ethyl acetat and phosphoric acid used for acidic. The extract was injected directly to gas chromatographic using butyric acid as internal standard. Calibration curve propionic acid range 25 – 1000 µg/mL. Coefissien of variation (CV) rates for spiked bakery produtcs were 1,36% and 99,81% (range 96,32 – 103,61%) for accuracy at ± 1000 mg/kg propionic acid, Limit detection (LoD) and limit quantitation (LoQ) by this method were 333,6537 mg/Kg and 635,5818 mg/Kg. Burger, hot dog, and sandwich buns from a local factory at Pontianak were analyzed and respectively rates less than the limit permitted by Indonesian regulations.